Assessment of Permanent First Molars in Children Aged 7 to 10 Years Old - Gelengul Urvasizoglu; Aybike Bas; Fatma Sarac; Peris Celikel; Fatih Sengul; Sera Derelioglu (MDPI AG, 2022)
Background: Dental caries is a chronic, infectious and preventable disease that is very common around the world. It has been observed that dental caries affect not only the majority of adults but also 60% to 90% of children. Permanent first molars (PFM) are the most commonly decayed teeth observed in children. Aim: The aim of this study is to evaluate the decayed, missing filled teeth (DMFT) scores of PFMs in the early post-eruptive stage, within the scope of the United Nations Agenda for 2030 Sustainable Development Goals, thereby raising awareness for the prevention and treatment of permanent tooth decay. Methods: This descriptive cross-sectional epidemiological study was conducted in Erzurum between the years 2015-2016 by collecting data from children aged 7-10 years (17,208). In addition to the decayed, filled and missing data of the students' 6-year-molars, their ages, genders, frequencies of both tooth brushing and dental office visits were evaluated. The relationship between the variables was analyzed with chi-square. Result: The present study analyzed the data of a total of 11,457 children, 5704 girls and 5753 boys with a mean age of 8.74 ± 1.18. There was a statistically significant difference between the PFMs 16, 26, 36 and 46 regarding the number of healthy, decayed, missing and restored teeth (p < 0.001). Conclusion: In this study, the prevalence of caries in the PFMs of children aged 7-10 years was 15.9% and the mean DMFT was 0.79 ± 1.39. This result showed that PFMs might develop carious lesions and even be lost within three years in the early post-eruptive stage.